School Social Workers and Extracurricular Activities: The Unanswered Questions About Potential Role Conflict - Jeffrey McCabe; Hannah Hagan (International Journal of School Social Work, 2023)
Abstract School social workers respond to students’ mental health needs from an education training perspective that defines set professional role boundaries in service provision that may differ from the multiple roles teachers have with students. One of those perspectives is a recognition of what may happen if a boundary crossing was to occur in a dual relationship with a client. Teachers are encouraged to take on a secondary role with students by coaching athletics or advising a club. Taking on dual roles with students has led to both increased job satisfaction and concerns regarding burnout for teachers. There is an absence of information that exists on what the experience has been of school social workers taking on secondary roles with students. Not having guidance for school social workers who elect to oversee extracurricular activities led the authors to explore what is the intended mission for the practice of school social work, how the existing literature on dual relationships may apply to school settings, and the findings from research conducted with teachers who take on dual roles with students. The recommendations provided are a need for data to establish what experience school social workers have with managing secondary roles and to not preclude school social workers from extracurricular activities when their presence can be of benefit to students and the school if dual relationships are properly managed.
Keywords: School social work; dual relationships; role conflicts; extracurricular activities; education policy